2019
DOI: 10.1145/3317679
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Power Management with Guaranteed Minimum Energy Utilization for Solar Energy Harvesting Systems

Abstract: In this work, we present a formal study on optimizing the energy consumption of energy harvesting embedded systems. To deal with the uncertainty inherent in solar energy harvesting systems, we propose the Stochastic Power Management (SPM) scheme, which builds statistical models of harvested energy based on historical data. The proposed stochastic scheme maximizes the lowest energy consumption across all time intervals while giving strict probabilistic guarantees on not encountering battery depletion. For situa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…The problem of computing the dynamic power management profile efficiently was explored in [14]. When ample historical data about the harvestable energy is available, a power management scheme proposed in [13] gives probabilistic guarantees that a minimal energy utilization will always be realized. Examples of uninterrupted environmental monitoring nodes operating over multiple years are given in [18], [19] for a high-mountain environment, in [20] for a remote field, and in [21] for a deep forest scenario.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The problem of computing the dynamic power management profile efficiently was explored in [14]. When ample historical data about the harvestable energy is available, a power management scheme proposed in [13] gives probabilistic guarantees that a minimal energy utilization will always be realized. Examples of uninterrupted environmental monitoring nodes operating over multiple years are given in [18], [19] for a high-mountain environment, in [20] for a remote field, and in [21] for a deep forest scenario.…”
Section: Related Workmentioning
confidence: 99%
“…In a realistic setting, a perfect estimate of future harvested energy is not available. Therefore, we employ the well known concept of model predictive control with a finite horizon, as used in [13], [29]. In contrast to the optimal clairvoyant solution shown before, this heuristic solution can cope with deviations between the predicted and actual harvested, or scheduled and actually used energy.…”
Section: Finite Horizon Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulation results showed that both resource allocation schemes lead to maximum utilization of harvested energy with minimum variability and upgrade the network performance. Ahmed et al presented a stochastic power management approach that leads to stochastic models of harvested solar irradiance on the basis of historical data. The work was focused on maximizing the minimum energy consumption in all time intervals and prevented battery depletion state.…”
Section: Node Level Power Managementmentioning
confidence: 99%
“…For selecting the optimal policy at run time, the sensor node deploys a duty-cycle adaptation mechanism that updates . The adaptation and energy estimation procedures used for this are beyond the scope of this work, we refer the reader to existing run-time adaptation methods [1,7,21,28]. To adapt the communication policy accordingly, the optimal selection policy with the activation interval closest to the new duty-cycle is loaded from the policy pool and forwarded to the run-time packet selection.…”
Section: Energy Harvesting Awarenessmentioning
confidence: 99%